Pemberdayaan Penyandang Disabilitas Dalam Mewujudkan Kemandirian Ekonomi (Kasus Di Desa Simbatan, Nguntoronadi, Magetan) - Mulyati, Tatik; Rohmatiah, Ahadiati; Lukito, Martin (JURNAL DAYA-MAS, 2019)
Persons with disabilities are part of citizens who have the same rights and obligations as those who do not have disabilities. But often their existence is less recognized by the community. Lack of access to education, employment and so on makes it difficult for people with disabilities to live a life like normal society in general.According to Law of Republic Indonesia Number 8 of 2016, persons with disabilities are those who experience physical, intellectual, mental, and / or sensory limitations for a long period of time who interact with the environment can experience obstacles and difficulties to participate fully and effectively with citizens. others are based on equal rights. One of the efforts so that persons with disabilities get the rights and obligations in the state is empowered. One form of empowerment is providing various skills training.The community service activities in Simbatan Magetan aim to find out the process of implementing various skills and assistance. Starting from how the implementation of skills training, such as what empowerment is done, how the level of success, as well as what becomes an obstacle in the empowerment process so that it can be independent.These skills training activities are endeavored to provide changes to persons with disabilities, those who were previously helpless became empowered, independent, brave, able to socialize well, even earn income from the skills they made, even though there were several obstacles faced.Â Keywordsâ€”: empowerment; persons with disabilities; independence.